Florid pseudoepitheliomatous hyperplasia related to tattoo: a case report - de Roeck, Aurelie (Int Wound J, 2012)
Pseudoepitheliomatous hyperplasia is a benign condition defined by an exuberant proliferation of the epithelium with downward progression into the dermis. It may occur in reaction to several conditions including chronic cutaneous wound. We describe an unusual case of a florid pseudoepitheliomatous hyperplasia mimicking a well‐differentiated squamous cell carcinoma, restricted to the red part of a rose tattoo.